Techno economic evaluation of MSW gasification for power generation: article - Mohd Sani, Ahmad Siddiq; Kasmuri, Nor Hazelah; Md Abul, Mohammad Asadullah (2017)
Energy recovery from biomass and municipal solid waste (MSW) by gasification technology has attracted significant interest because it satisfies a key requirement of environmental sustainability by producing near zero emissions. Though it is not a new technology, studies on its integrated process simulation and analysis are limited, in particular for (MSW) gasification. This paper develops a gasification process by using the Advanced System for Process Engineering (Aspen) Plus software for evaluation of its technology performance. Using the develop model.computational model was developed on the basis of Gibbs free energy minimization. The model of gasification process the effect of operating conditions, gasification temperature, air to fuel ratio and moisture content. Gasification temperature and air to fuel ratio affect the synthesis gas produce while moisture content only gave minimal change toward the gas composition. By using pilot scale downdraft gasifier, tar was collected and analysed. Cleaner gas collected after flow through series of filter bed consists of sawdust and activated carbon. In terms of economic, all the calculation and result was based from small scale of 10 tonne/day MSW plant. The operation of this plant can generate RM 1.124 million of revenue per year with payback period of 6.85. The rate of return of investment (ROROI) is positive at 6.31% per annum and cumulative cash flow is positive.